SHARING MASYARATAKAT DESA WISATA: PENINGKATAN PERSONALITI BERBASIS KEARIFAN LOKAL - Yusuf Tojiri; Rusdian, Suca (Jurnal Masyarakat Berdikari dan Berkarya (Mardika), 2024)
Abstract. The service activity "Travel Village Community Sharing: Personality Improvement Based on Local Wisdom" aims to strengthen the potential of local wisdom-based tourism in the Sindangkasih Tourism Village, Garut Regency. One of the main components of this activity is personal training and local wisdom for village communities. This training aims to increase self-awareness, skills and attitudes in accordance with local wisdom values ​​in the tourism context. Through a participatory approach, the training succeeded in increasing community awareness about the cultural values ​​and local wisdom of their village. Trainees also develop practical skills in the tourism industry, such as communication and marketing skills. Additionally, they are starting to adopt a caring attitude towards the environment and sustainability. This training activity has a positive impact on the development of village tourism, by preparing the community to become part of the growing tourism industry. The conclusion of this activity emphasizes the importance of active community participation in developing local wisdom-based tourism, as well as the need to implement training results in daily practice.